THE INJUSTICE OF DISTRIBUTING MARITAL PROPERTY (HARGA GINI GONO) IN DIVORCE CASES - Sri Hariati & Musakir Salat (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
After a divorce happened does not mean the family has completed all are problems, but still leave residual problems such as child marriage ( if have children ) and property acquired during the marriage, property acquired during marriage is still related to what is called the joint property or property known Gono gini, disputed the division of joint property, can generally be described that the dispute resolution division of joint property, the division of matrimonial property ( assets gono gini ) to the wife in a divorce often lead to inequality in various aspects especially in the division of matrimonial property ( assets gono gini ) . Observations did about the value of unfairness in the division of joint property in the Village Suralaga in Suralaga District of East Lombok. Inequities in the division of matrimonial property on divorce post implied from several factors including the cultural ideology of patriarchy is still evolving at this time, but it also inequities in the division of joint property caused by the system of inheritance law on which the decision is still indicated the existence of discrimination against women as the dominant party gets unfairness in the process of division of joint property, this occurs because the shape of the existing policy.Keywords : Injustice , Treasure Gono-Gini and Divorce